Heidegger and Adorno: prolegomena to reconstruction of a dialogue, which never appeared - Karpenko, Andriy (Skhid, 2014)
Discourse of Heidegger studies in contemporary Ukraine proves insufficient attention to the world legacy in understanding and interpreting complex thinking of the great German philosopher. In order not to yield the temptations of direct reading, we are advancing the imperative of precise mediation of historical research of Heidegger's philosophy by methods and instruments, which would conform with the actual context of philosophical process worldwide. This article aims to accomplish logical reconstruction of the interspace between discourses of Martin Heidegger and Theodore Adorno. This interspace of the potential dialogue between the two philosophers can be seen not as a gap but rather a joint of one and the same thought being developed in two opposite directions. Adornian approach to understanding Heidegger's thinking is viewed as a methodological model for the contemporary needs of the historiographical hermeneutics of Heidegger's philosophy. In the terms of ideological criticism Heideggerian conceptuality assume the form of a jargon, which stylistically derives from archaistic tendencies of the late Romanticism. Unlike P. Bourdieu, Adorno does not aim to reveal the social background of this proximity between existential philosophy and cultural conservatism of the Weimar epoch, but rather he persists in deconstructing the key concepts of Heidegger's philosophy, so that he would reveal its neutralizing and metaphysical effects. In Adorno's transcription of the difference between onticity and ontology, the latter appears as a form of reification, and consequently as a philosophical form of ideology preoccupied with the conservative claims to preserve the existing order. The conservative move of Heidegger's logic consists in subjugation of Dasein to being, where being is conceptually charged as a secularized deity. Heidegger's possible response to Adorno's invectives should certainly avoid Heideggerian language. It is necessary to obtain an outer position to both discourses, if we want to elicit novel forms of thought.